2003
DOI: 10.1021/ja0351241
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of (2S,3R)-Capreomycidine and the Total Synthesis of Capreomycin IB

Abstract: A 27 step total synthesis of the tuberculostatic macrocyclic peptide antibiotic capreomycin IB has been accomplished. The synthesis features the use of an enolate-aldimine condensation between a chiral glycine aluminum enolate and the benzyl imine of 3-tert-butyldimethylsiloxy-propanal as a means of preparing the cyclic guanidine amino acid (2S,3R)-capreomycidine. Additionally, a Hofmann rearrangement was exacted on a late-stage pentapeptide in order to transform an asparagine residue into a diaminopropanoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 38 publications
0
39
0
1
Order By: Relevance
“…Eventually we found that reduction of the azide with activated zinc 10 and ammonium formate in MeOH for 7 h at 25 °C proceeded cleanly to give polar amine 12b that was used without purification. 11a Coupling of 12b with Boc-protected S -methylisothiourea 13 using Et 3 N and AgNO 3 4b, 12 in DMF for 2 h at 0 °C and 5 h at 25 °C afforded protected guanidine 14b in 60% yield from 11b . Deprotection of 14b by stirring in 10:1 CH 2 Cl 2 /TFA for 8 h at 25 °C removed the Boc protecting groups providing phidianidine B ( 1b ) in 92% yield.…”
mentioning
confidence: 99%
“…Eventually we found that reduction of the azide with activated zinc 10 and ammonium formate in MeOH for 7 h at 25 °C proceeded cleanly to give polar amine 12b that was used without purification. 11a Coupling of 12b with Boc-protected S -methylisothiourea 13 using Et 3 N and AgNO 3 4b, 12 in DMF for 2 h at 0 °C and 5 h at 25 °C afforded protected guanidine 14b in 60% yield from 11b . Deprotection of 14b by stirring in 10:1 CH 2 Cl 2 /TFA for 8 h at 25 °C removed the Boc protecting groups providing phidianidine B ( 1b ) in 92% yield.…”
mentioning
confidence: 99%
“…The enantiopure Ni(II) complex of benzophenone a-imino glycinate and the aluminum enolate of a chiral oxazinone derived from glycine have been used for the synthesis of fluorinated 2,3-diamino acids (98% d.e.) [7] and capreomycidine [8], respectively. Chiral imines can participate as inductors of asymmetry in the Mannich process.…”
Section: Reaction Of Glycinates and Related Nucleophiles With Electromentioning
confidence: 99%
“…Demong and Williams reported the asymmetric synthesis of capreomycidine (six steps, 28% yield) en route to his total synthesis of capreomycin IB [247,248]. By invoking an enolate-aldimine strategy, condensation of benzylimine 179 with the lithium enolate of chiral glycinate 180 resulted in an inseparable 3.3 : 1 mixture of diastereomers 181 epimeric at the b-carbon (Scheme 5.45).…”
Section: Noncoded Amino Acids With Elaborate Side-chains J209mentioning
confidence: 99%